RHEUMATOID ARTHRITIS: A MODERN VIEW OF THE PROBLEM AND PECULIARITIES OF REHABILITATION MEASURES - Nekhanevych, O. B.; Kaniuka, Ye. V. (Rehabilitation and Recreation, 2023)
The purpose of the paper was to highlight the peculiarities of the use of rehabilitation measures in rheumatoid arthritis. Material and methods: theoretical analysis, synthesis, generalisation of scientific and methodological literature sources. The article highlights the main links in the etiology, pathogenesis, characteristic symptoms of rheumatoid arthritis and the prevalence of the disease in Ukraine and the world in general. The article describes the stages of rheumatoid arthritis and modern approaches to the use of complex pathogenetic therapy. It is noted that numerous clinical data indicate a high degree of impairment of physical function and physical activity among patients with rheumatoid arthritis due to the formation of functional joint failure and impaired mobility. It has been found that the severity of the condition of a patient with rheumatoid arthritis is due to progressive polyarthritis, accompanied by pain and deterioration of physical functions, significantly affecting the quality of life of patients. The article summarises and presents current views and trends in the use of rehabilitation measures for patients with rheumatoid arthritis. An analysis of physical therapy/rehabilitation programmes for patients with rheumatoid arthritis has shown that today the traditional foundations of treatment and rehabilitation of these patients are laid. It is noted that recently new methods and technologies have been developed in the treatment of patients with rheumatoid arthritis, which emphasise the need for the integrated use of physical therapy/rehabilitation. It is emphasised that the process of rehabilitation and social adaptation of patients with rheumatoid arthritis should include appropriate rehabilitation measures and technologies that would adapt the patient to everyday life, domestic and professional conditions by improving the quality of life. It is proved that this problem is still relevant, and the issue of the integrated use of rehabilitation measures in the process of rehabilitation treatment requires new scientific developments that will help reduce the number of negative consequences of the disease that affect the quality of life of patients. At the present stage, there is a need for further research, improvement and a comprehensive strategy for the implementation of rehabilitation measures and technologies for patients with rheumatoid arthritis to adapt them to everyday life, domestic and professional conditions by improving their quality of life.